South-South Dialogues around Buen Vivir-Centric Design - Diana Albarrán González; Angus Donald Campbell (Diseña, 2022)
Using a dialogic methodology, in this article we discuss our doctoral research experiences and positionalities in two different contexts from the Global South, working with historically marginalized communities. The first voice, originating in Mexico, explored decolonizing design and Mayan textile knowledges in collaboration with a women-led collective in the highlands of Chiapas. The second voice, which originated in South Africa, collaboratively explored technological innovation by small-scale urban farmers. The dialogue reflects on uno con el todo, colectividad, resource(ful), pluriversal, and equilibrium as Buen Vivir- Centric design guiding principles to reflect on our studies. We discuss the learnings and transformations in our design research from dominant approaches towards Indigenous and endogenous ways of knowing, being, and making.